Stereolithography Apparatus Evolution: Enhancing Throughput and Efficiency of Pharmaceutical Formulation Development - Carlo Curti; Daniel J. Kirby; Craig A. Russell (MDPI AG, 2021)
Pharmaceutical applications of 3D printing technologies are growing rapidly. Among these, vat photopolymerisation (VP) techniques, including Stereolithography (SLA) hold much promise for their potential to deliver personalised medicines on-demand. SLA 3D printing offers advantageous features for pharmaceutical production, such as operating at room temperature and offering an unrivaled printing resolution. However, since conventional SLA apparatus are designed to operate with large volumes of a single photopolymer resin, significant throughput limitations remain. This, coupled with the limited choice of biocompatible polymers and photoinitiators available, hold back the pharmaceutical development using such technologies. Hence, the aim of this work was to develop a novel SLA apparatus specifically designed to allow rapid and efficient screening of pharmaceutical photopolymer formulations. A commercially available SLA apparatus was modified by designing and fabricating a novel resin tank and build platform able to 3D print up to 12 different formulations at a single time, reducing the amount of sample resin required by 20-fold. The novel SLA apparatus was subsequently used to conduct a high throughput screening of 156 placebo photopolymer formulations. The efficiency of the equipment and formulation printability outcomes were evaluated. Improved time and cost efficiency by 91.66% and 94.99%, respectively, has been confirmed using the modified SLA apparatus to deliver high quality, highly printable outputs, thus evidencing that such modifications offer a robust and reliable tool to optimize the throughput and efficiency of vat photopolymerisation techniques in formulation development processes, which can, in turn, support future clinical applications.